Factors affecting the decision to initiate antiretroviral therapy in the era of treatment-as-prevention: synthesis of evidence from qualitative research in high-income settings. Issue 4 (3rd April 2019) - Hollingdrake, Olivia; Lui, Chi-Wai; Mutch, Allyson; Dean, Judith; Howard, Chris; Fitzgerald, Lisa
ABSTRACT: The emergence of treatment-as-prevention has made early initiation of antiretroviral treatment (ART) a "universal" policy. This review synthesizes qualitative research findings on barriers and facilitators of ART initiation in Organization for Economic Co-operation and Development (OECD) countries published since 2010. Ten articles describing seven research studies were included in the review. Findings confirmed ART initiation as a complicated process involving careful deliberation of the personal risks and benefits of treatment within the broader contexts of everyday life for people living with HIV (PLHIV). They also highlight interpersonal dynamics and concern for the public as increasingly important factors in shaping the decision to initiate treatment. The review provides valuable information for understanding treatment behaviour and maximizing treatment options brought forth by new biomedical advances.